Molecular Pathways Controlling Autophagy in Pancreatic Cancer - New, Maria; Van Acker, Tim; Long, Jaclyn S.; Sakamaki, Jun-ichi; Ryan, Kevin M.; Tooze, Sharon A. (Frontiers in Oncology, 2017)
Pancreatic ductal adenocarcinoma (PDAC) is one of the few cancer types where the 5 year survival rate shows no improvement. Despite conflicting evidence, the majority of data points to an essential role for autophagy in PDAC growth and survival, in particular constitutively activated autophagy can provide crucial fuel to PDAC tumour cells in their nutrient-deprived environment. Autophagy, which is required for cell homeostasis, can both suppress and promote tumourigenesis and tumour survival in a context-dependent manner. Protein by protein, the mystery of how PDAC abuses the cell’s homeostasis system for its malignant growth has recently begun to be unravelled. In this review, we focus on how autophagy is responsible for growth and development of PDAC tumours and where autophagy and the mechanisms controlling it fit into PDAC metabolism. Understanding the range of pathways controlling autophagy and their interplay in PDAC could open the way for new therapeutic avenues.